A Case Study on the Eco-Efficiency Performance of a Composite Processing Industry: Evaluation and Quantification of Potential Improvements - Ribeiro, M.C.S.; Castro, A.C.M.; Silva, F.J.G.; Meixedo, J.P.; Oliveira, L.; Alvim, M.R.; Fiúza, A.; Dinis, M.L. (Journal of Research Updates in Polymer Science, 2013)
In this study, an attempt was made in order to measure and evaluate the eco-efficiency performance of a pultruded composite processing company. For this purpose the recommendations of World Business Council for Sustainable Development (WCSD) and the directives of ISO 14301 standard were followed and applied. The main general indicators of eco-efficiency, as well as the specific indicators, were defined and determined. With basis on indicators’ figures, the value profile, the environmental profile, and the pertinent eco-efficiency ratios were established and analyzed. In order to evaluate potential improvements on company eco-performance, new indicators values and eco-efficiency ratios were estimated taking into account the implementation of new proceedings and procedures, at both upstream and downstream of the production process, namely: i) Adoption of a new heating system for pultrusion die-tool in the manufacturing process, more effective and with minor heat losses; ii) Recycling approach, with partial waste reuse of scrap material derived from manufacturing, cutting and assembly processes of GFRP profiles. These features lead to significant improvements on the sequent assessed eco-efficiency ratios of the present case study, yielding to a more sustainable product and manufacturing process of pultruded GFRP profiles.